The Impact of Employer Branding on Attracting and Retaining Generation Z Talent In Saudi Arabia’s Oil and Gas Industry - Rizal Agianno (Green Publisher Indonesia, 2025)
This study examines the impact of employer branding on attracting and retaining Generation Z talent in Saudi Arabia’s oil and gas industry within the context of Vision 2030. As Saudi Arabia diversifies its economy away from oil dependence, emerging sectors supported by Vision 2030—such as renewable energy, tourism, and electric vehicles—pose competitive threats to traditional oil and gas companies in attracting young talent. Using a quantitative approach with 100 respondents from Generation Z in Saudi Arabia, this research employs multiple regression analysis to identify which employer branding dimensions most significantly influence Generation Z’s intention to apply and employee retention in the oil and gas sector. The study measures four independent variables: Employee Growth Need Strength, Psychological Contract, Perception of Organizational Support, and Organizational Identification, against two dependent variables: Intention to Apply and Employee Retention. Results reveal that Psychological Contract (β = 0.399, p < 0.001 for intention to apply; β = 0.461, p < 0.001 for retention) and Organizational Identification (β = 0.307, p = 0.001 for intention to apply; β = 0.270, p = 0.001 for retention) are the most significant factors influencing both outcomes. The findings suggest that oil and gas companies should prioritize transparent career development programs, competitive compensation packages, work-life balance initiatives, and strong organizational identity to attract and retain Generation Z talent. This research contributes practical insights for human resource strategies in the oil and gas sector during Saudi Arabia’s economic transformation.